Health Behaviors of Student Community Research Partners When Designing and Implementing a Healthy Lifestyle Intervention on College Campuses - Makenzie L. Barr; Sarah E. Colby; Kristin Riggsbee; Krista Leischner; Anne E. Mathews; Melissa J. Vilaro; Kendra K. Kattelmann; Melissa D. Olfert (Behavioral Sciences, 2018)
Few studies work with college students as equal partners in all aspects of Community-Based Participatory Research (CBPR) and even less evaluate behaviors of those college partners. The current study aimed to examine health behaviors of students by designing and implementing a peer-led, social marketing campaign (Get Fruved) to promote healthier lifestyles on their campuses. Enrolled students (n = 376) were trained to either design and implement a health promotion intervention (Social Marketing and Environmental Interventionists; SMEI, n = 78), be peer mentors (PM; n = 205), or serve as control participants (n = 93). Students’ behaviors (dietary, activity, and stress) and anthropometrics were assessed at baseline, 6 months, and 12 months. The population was predominately Caucasian, female, and between 19 and 20 years old. On average, fruit and vegetable consumption slightly decreased across all time points for each group with control at a larger decline. Students International Physical Activity Questionnaire (IPAQ) scores showed students met recommended amounts of activity throughout the intervention, with males reporting higher activity levels. Cohen’s Perceived Stress Scale (PSS) analyses indicated 19 year olds had higher stress along with females had higher than males. Students involved in a CBPR approach to be trained, design, and implement a lifestyle intervention can achieve maintenance of health behaviors throughout a college year when compared to control students.